Investigation of the scattering of electrons by ions in the plasma of inertial confinement fusion in a magnetic field - Issanova, M.K.; Kodanova, S.K.; Bastykova, N.Kh.; Kenzhebekova, A.I. (Recent Contributions to Physics, 2021)
In this paper, the processes of electron-ion scattering in the plasma of inertial confinement fusion in a magnetic field were studied. Collisions between an electron and an ion that interact via the Yukawa potential were investigated. Also, the Coulomb logarithm in a dense plasma in a magnetic field was calculated. The effect of taking into account the magnetic field on the scattering angles, the scattering cross-section and the Coulomb logarithm are studied. From the results obtained, it is established that taking into account the magnetic field led to a non-monotonic change in the scattering angle and a decrease in the scattering cross-section for weak particle interactions. It is also revealed that for large values of the interaction parameter , the magnetic field does not affect the value of the Coulomb logarithm. Thus, the obtained results allow us to study the effect of taking into account the magnetic field on the processes of electron scattering on an ion in the approximation of pair collisions in an external constant magnetic field in a dense plasma.